Primary thyroid lymphoma: a rare malignancy in the head and neck - Mamat Nasir, Mohd Shaiful Nizam; Susibalan, Bathma Dhevi; Abu Bakar, Muhammad Nasri; Yusof, Suhaimi; Selimin, Arfahiza; Abdullah, Kahairi; Mohamad, Irfan (Penerbit Universiti Sains Malaysia, 2018)
Primary thyroid lymphoma is a relatively uncommon pathology of the thyroid gland that mainly occurs in elderly females. We describe a rare case of B-cell thyroid lymphoma in a young healthy male. It is an important diagnosis to be considered in patients presenting with a rapidly enlarging neck mass as its management is different from other differentiated thyroid carcinoma which require total thyroidectomy plus adjuvant radioactive iodine ablation. Our report emphasizes the need for clinical awareness leading to early detection, followed by early multidisciplinary management.